Study of the reaction time to an external stimulus and its influence on math and verbal ability for Santa Ana high school students of Bellavista - Callao - Chui Betancour, Heber Nehemías (2014)
This paper show results of quantitative study in a first approximation, of the reaction time to an external stimulus and its influence on math and verbal ability for Santa Ana high school students of Bellavista – Callao. Finding evidence of an inverse relationship of two variables, which are concluded by multivariate statistical methods.